2017
DOI: 10.1094/mpmi-04-17-0096-r
|View full text |Cite
|
Sign up to set email alerts
|

Sinorhizobium meliloti Chemotaxis to Multiple Amino Acids Is Mediated by the Chemoreceptor McpU

Abstract: The legume symbiont Sinorhizobium meliloti is chemoattracted to compounds exuded by germinating seeds of its host alfalfa. This response is mainly mediated by the S. meliloti chemoreceptor McpU. McpU also has a prominent contribution in sensing a synthetic amino acid (aa) mixture mimicking the amounts and composition observed in seed exudate. Here, we used the hydrogel capillary assay to quantify chemotactic responses of S. meliloti to individual aa exuded by germinating alfalfa seeds and to define the role of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
30
2

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 43 publications
1
30
2
Order By: Relevance
“…For example, malic acid that is present both in the root exudates of Arabidopsis thaliana and tomato, is a chemoattractant for B. subtilis (Rudrappa et al, ), R. pseudosolanacearum (Hida et al, ) and P. fluorescens (de Weert et al, ; Gupta Sood, ) and contributes to root colonization. Further examples illustrate that several of the other key attractants (fumaric and gluconic acids, Lys, Ser and Ala) that were identified in exudates of Cicer arietinum L., tomato and alfalfa, were also important attractants for rhizospheric microorganisms (Gitte et al, ; de Weert et al, ; Gupta Sood, ; Glekas et al, ; Webb et al, ). It appears that organic acids (especially the tricarboxylic acid cycle intermediates) and amino acids serve frequently as chemoattractants for various rhizobacteria (Bardy et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, malic acid that is present both in the root exudates of Arabidopsis thaliana and tomato, is a chemoattractant for B. subtilis (Rudrappa et al, ), R. pseudosolanacearum (Hida et al, ) and P. fluorescens (de Weert et al, ; Gupta Sood, ) and contributes to root colonization. Further examples illustrate that several of the other key attractants (fumaric and gluconic acids, Lys, Ser and Ala) that were identified in exudates of Cicer arietinum L., tomato and alfalfa, were also important attractants for rhizospheric microorganisms (Gitte et al, ; de Weert et al, ; Gupta Sood, ; Glekas et al, ; Webb et al, ). It appears that organic acids (especially the tricarboxylic acid cycle intermediates) and amino acids serve frequently as chemoattractants for various rhizobacteria (Bardy et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The size of the ligand-binding domains of S. meliloti chemoreceptors varies greatly between 160 and 390 amino acid (aa) residues (30). Our group has shown that McpU and McpX play a role in host interaction by sensing plant-derived amino acids and quaternary ammonium compounds, respectively (31)(32)(33)(34). However, the function of the remaining six chemoreceptors is not known.…”
mentioning
confidence: 99%
“…Chemotaxis has been thoroughly established as a critical facet of nodule occupancy and competition in symbiotic rhizobacteria (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)35). Plants exude a plethora of compounds, such as amino acids, sugars, organic acids, flavonoids, lipids, and ions (20,21,(36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%
“…The functions of two of the eight chemoreceptors involved in S. meliloti chemotaxis have been elucidated. McpU is a general amino acid receptor, sensing all nonacidic proteogenic amino acids, as well as several nonproteogenic amino acids (16,25). McpX senses quaternary ammonium compounds (QACs), such as glycine betaine, trigonelline, and choline, through direct binding, and it is the first QAC chemoreceptor described in bacteria (17).…”
mentioning
confidence: 99%